Green Pulsed Electric Field-Assisted Extraction Method of Total Carotenoid Carrot Pulp Using Olive Oil as Solvent - Angky Wahyu Putranto; Bambang Dwi Argo; Susinggih Wijana (Program Pascasarjana Universitas Brawijaya, 2014)
Carrot (Daucus carrota L.) pulp as a by-product of carrot juice processing, containing a high content of total carotenoid. It was necessary for the extraction that can be used to other food products enriched by carotenoid. Green extraction method of total carotenoid from carrot pulp assisted by Pulsed Electric Field (PEF) which had been designed was well determined in this study. Extra virgin olive oil was applied as a substitute to organic solvent which was in line with green extraction concept. The oil based extraction process by PEF-assisted was compared not only with oil based extraction using both olive oil and crude palm oil without PEF-assisted but also compared with conventional solvent extraction using 96% ethanol as solvent. The present study has been determined that the PEF-assisted extraction method using olive oil as solvent had highest of total carotenoid extract (34.16+1.02 µg/g) when compared with other methods. This method under condition in carrot pulp-oil ratio was 1: 10 (w/v), treatment time was 10 second and electric field strength was 2.5kV/cm Keywords: carrot pulp, green extraction, pulsed electric field, total carotenoid